2014
DOI: 10.1155/2014/352862
|View full text |Cite
|
Sign up to set email alerts
|

Clonality and Resistome Analysis of KPC-ProducingKlebsiella pneumoniaeStrain Isolated in Korea Using Whole Genome Sequencing

Abstract: We analyzed the whole genome sequence and resistome of the outbreak Klebsiella pneumoniae strain MP14 and compared it with those of K. pneumoniae carbapenemase- (KPC-) producing isolates that showed high similarity in the NCBI genome database. A KPC-2-producing multidrug-resistant (MDR) K. pneumoniae clinical isolate was obtained from a patient admitted to a Korean hospital in 2011. The strain MP14 was resistant to all tested β-lactams including monobactam, amikacin, levofloxacin, and cotrimoxazole, but suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
5
25
0
Order By: Relevance
“…This suggests that certain ancestral plasmids are particularly well suited to Enterobacteriaceae, such as K. pneumoniae, and are good candidates for sustaining the presence of bla KPC through multiple independent insertion and transposition events. This is further supported by a recent study in Korea that demonstrated that ancestral plasmids were present among the ST258 isolates found in various geographical regions and were obtained as early as 2002 (87).…”
Section: Plasmids Associated With K Pneumoniae St258 With Bla Kpcsupporting
confidence: 71%
“…This suggests that certain ancestral plasmids are particularly well suited to Enterobacteriaceae, such as K. pneumoniae, and are good candidates for sustaining the presence of bla KPC through multiple independent insertion and transposition events. This is further supported by a recent study in Korea that demonstrated that ancestral plasmids were present among the ST258 isolates found in various geographical regions and were obtained as early as 2002 (87).…”
Section: Plasmids Associated With K Pneumoniae St258 With Bla Kpcsupporting
confidence: 71%
“…This suggests that certain ancestral plasmids are particularly well suited to Enterobacteriaceae such as K. pneumoniae and are good candidates for sustaining the presence of bla KPC through multiple independent insertion and transposition events. This is further supported by a recent study from South Korea that demonstrated that ancestral plasmids were present among ST258 isolates from various geographical regions and were obtained as early as 2002 (143).…”
Section: Plasmids Associated With K Pneumoniae St258supporting
confidence: 70%
“…A recent study that used next-generation sequencing with long reads examined the contents on plasmids in a single ST258 isolate. Those investigators identified four plasmids containing 24 different resistance genes (142) , and bla TEM-1 ), fluoroquinolone resistance (i.e., oqxA and oqxB), macrolide-lincosamide-streptogramin B resistance (i.e., mphA), chloramphenicol resistance (i.e., catA1), trimethoprim resistance (i.e., dfrA12), and sulfonamide resistance (i.e., sul1) (142,143). ST258 isolates can also decrease the number of porin channels, which leads to nonsusceptibility to additional classes of antimicrobial drugs, leaving clinicians with very limited treatment options (144).…”
Section: Recent Developments Pertaining To K Pneumoniae St258mentioning
confidence: 99%
“…The carbapenem resistance of the isolate that we uncovered in this study may not be due to the horizontal transfer of the plasmid and clonal spread because similar plasmids carrying bla KPC-2 have not been reported and because the K. pneumoniae isolate carrying pKPC-DK05 has a novel genotype unknown to produce K. pneumoniae carbapenemase (KPC) (5)(6)(7)(8). Thus, we can speculate that our carbapenemase-producing K. pneumoniae isolate emerged via incorporation of Tn4401 into the prevailing plasmid.…”
mentioning
confidence: 82%